Calidad fisicoquímica de Cisplatino polvo de un laboratorio farmacéutico nacional - Hidalgo Rodriguez, Lanman Larry (2015)
In this report the evaluation of the physicochemical quality of three batches of cisplatin powder as raw material for a national pharmaceutical laboratory was performed by physical parameters such as sample description, solubility and crystallinity; and chemical parameters as molecular identification by infrared spectroscopy (IR), high performance liquid chromatography (HPLC) and thin layer chromatography; also specific tests such as Karl Fischer´s water determination, purity ratio of ultraviolet (UV) and tricloroaminoplatinato limit. Physicochemical parameters meet established specifications from analysis protocol of quality control department for cisplatin powder as raw material